2006
DOI: 10.5194/acpd-6-9823-2006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Box-Air-Mass-Factors and Radiances for Multiple-Axis Differential Optical Absorption Spectroscopy (MAX-DOAS) Geometries calculated from different UV/visible Radiative Transfer Models

Abstract: Abstract. The results of a comparison exercise of radiative transfer models (RTM) of various international research groups for Multiple AXis Differential Optical Absorption Spectroscopy (MAX-DOAS) viewing geometry are presented. In contrast to previous comparison exercises, box-air-mass-factors (box-AMFs) for various atmospheric height layers were modelled, which describe the sensitivity of the measurements as a function of altitude. In addition, radiances were calculated allowing the identification of potenti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 20 publications
0
51
0
Order By: Relevance
“…RTMs were reviewed by Hendrick et al (2006) and Wagner et al (2007). Different RTMs differ in the way of simulating photon transverse process in the atmosphere, the treatment of the Earth's sphericity, the way of considering aerosol scattering, the inclusion of the photo-enhancement of short lifetime species, etc.…”
Section: Developed a Technique To Use The O 4 Absorption Tomentioning
confidence: 99%
See 1 more Smart Citation
“…RTMs were reviewed by Hendrick et al (2006) and Wagner et al (2007). Different RTMs differ in the way of simulating photon transverse process in the atmosphere, the treatment of the Earth's sphericity, the way of considering aerosol scattering, the inclusion of the photo-enhancement of short lifetime species, etc.…”
Section: Developed a Technique To Use The O 4 Absorption Tomentioning
confidence: 99%
“…In this study we concentrate on the effect of aerosols and investigate only measurements under mostly cloud free conditions. Over the last years, different radiative transfer models have been developed (see Wagner et al, 2007, and references therein). We used McArtim (Deutschmann, 2009), which is a backward Monte-Carlo model.…”
Section: Developed a Technique To Use The O 4 Absorption Tomentioning
confidence: 99%
“…In this study we use the full spherical Monte-Carlo atmospheric radiative transfer model McArtim (Monte Carlo Atmospheric Radiative Transfer and Inversion Model) (Deutschmann, 2008); it was compared to various other radiative transfer models (Wagner et al, 2007a) and excellent agreement was found. McArtim allows the simulation of ensembles of individual photon trajectories for a given Table 2.…”
Section: Radiative Transfer Modellingmentioning
confidence: 99%
“…This method is so-called "geometric approximation". However, geometric approximation of AMF could result in large errors under high aerosol load conditions (Wagner et al, 2007). In addition, relative azimuth angle, defined as the angle between the viewing direction and the sun, also plays an important role in the AMF calculation.…”
Section: Determination Of the Tropospheric Vcd 145mentioning
confidence: 99%